Proposta de indicadores para elaboração de plano de gestão de logística sustentável (PLS): pesquisa-ação no CINDACTA II - Carvalho, Luís Gustavo (2016)
The PLS are planning tools that provide the body or entity the establishment of sustainability practices and rationalization of spending and processes in Public Administration, being regulated from Decree 7.746 of June 5, 2012 and in the Normative Instruction No. 10 of SLTI / MOG of 12 November 2012, that establish the plans under the Federal Public Administration. However, the indicators present in the PLS, based on this instruction, are not sufficient for the preparation, evaluation and monitoring appropriate in compliance with the dimensions of the sustainable development. Thus, the overall objective of the study is to propose the complementation of indicators for use in PLS of public institutions in compliance with the dimensions of the sustainable development. The study comes on the Second Integrated Center of Air Defense and Air Traffic Control (CINDACTA II. The research is applied as to its purpose and exploratory as to its general and specific objectives. The applied methodology uses the process of action research by the Management Committee of the Plan in the Organization. In this study, the concepts of Public Management and Sustainability are explored, Plans of Sustainable Logistics Management (SLP), the dimensions and indicators of sustainable development. The theoretical framework was based on bibliographical and documentary research in the Reference in Legislation and content analysis of 66 SLP cataloged by the Government Procurement Portal of the federal government. As a result of the research, 70 indicators were proposed for use in the preparation of the Organization SLP, distributed on the thematics axis proposed by the Environmental Agenda in Public Administration (A3P): Rational Use of Natural Resources and Public Goods (25 indicators), Proper management of generated waste (13 indicators), Quality of Life in the Workplace (9 indicators), Servers Training awareness (12 indicators) and Sustainable bidding (11 indicators). After the elaboration of the indicators proposal, we proceeded to the rating of them, and the Sustainable Development Indicators IBGE, Brazil 2015 were used as reference, which includes the environmental, social, economic and institutional dimensions, following the model proposed by the Commission for Sustainable Development of the United Nations (CSD). From this indicators classification, the following quantitative were obtained: 49 related to the economic dimension, 40 indicators corresponding to the environmental dimension, 32 corresponding to the institutional dimension and 17 indicators related to the social dimension. These quantitatives come from the multiple compliance with the dimensions of sustainable development, where an indicator can be related to more than one dimension, simultaneously. Although, the document of Sustainable Development Indicators, IBGE, Brazil 2015, has been used, there was difficulty in the final classification of the indicators, given that this model provides information in macroscale and it demands greater capillarity to allow association with the indicators for the SLP in organizational scope. This study adds information to the construction of indicators for use in Sustainable Logistics Management Plans, considering the dimensions of the sustainable development.